Respuesta :

Answer:

f'(x) = 2x + [tex]\frac{12}{x^{4} }[/tex]

Step-by-step explanation:

differentiate using the power rule

[tex]\frac{d}{dx}[/tex] ( a[tex]x^{n}[/tex] ) = na[tex]x^{n-1}[/tex]

Given

f(x) = x² - [tex]\frac{4}{x^3}[/tex] + 9 = x² - 4[tex]x^{-3}[/tex] + 9 , then

f'(x) = 2x + 12[tex]x^{-4}[/tex] = 2x + [tex]\frac{12}{x^{4} }[/tex]

Answer:

[tex]f'(x)=2x+\dfrac{12}{x^4}[/tex]

Step-by-step explanation:

[tex]f(x)=x^2-\dfrac{4}{x^3}+9[/tex]

Apply exponent rule [tex]\dfrac{1}{a^b}=a^{-b}[/tex]:

[tex]\implies f(x)=x^2-4x^{-3}+9[/tex]

Differentiate using the power rule [tex]\frac{d}{dx}(x^a)=a \cdot x^{a-1}[/tex] :

[tex]\implies f'(x)=2 \cdot x^{2-1}-(-3)4x^{-3-1}+0[/tex]

[tex]\implies f'(x)=2x+12x^{-4}[/tex]

[tex]\implies f'(x)=2x+\dfrac{12}{x^4}[/tex]